Research on Internet Insurance Performance Efficiency of Life Insurance Company in China Using Data Envelopment Analysis - wang, da (Advances in Social Sciences Research Journal, 2016)
In these years, the revenue of premium from the Internet is increasing constantly and the Internet Insurance is developing at an amazing speed. However, how about the operation efficiency of Internet Insurance? Basing on the situation of revenue of premium from the Internet, this paper selects the top 10 Life Insurance Companies in China as the research samples. Using Data Envelopment Analysis and choosing both financial and non-financial variables, this paper makes a research on the Internet Insurance performance efficiency of Life Insurance Companies. The results show that in the early development period, the performance efficiency of Internet Insurance is normally low and the input of fixed assets does less to the performance efficiency than other two inputs. And this paper put forwards that insurance companies should take use of the official website to improve the performance efficiency of the Internet.